2012
DOI: 10.3892/etm.2012.575
|View full text |Cite
|
Sign up to set email alerts
|

Role of elevated liver transaminase levels in the diagnosis of liver injury after blunt abdominal trauma

Abstract: Abstract. The liver is the second most commonly injured organ following blunt abdominal trauma. The stable patient with minimal physical findings with a history of blunt abdominal trauma presents a challenge for diagnosis of liver injury. This study was conducted to determine the usefulness of hepatic transaminases in predicting the presence of liver injury and its severity following blunt abdominal trauma. In this retrospective study, we included all patients who had sustained blunt abdominal injury and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
5
32
1
Order By: Relevance
“…A study conducted by Tian et al found a trend that the more severe the liver injury of the patients, the higher the liver enzyme levels, but their study further demonstrated that patients with elevated ALT>100 U/l, AST>113 U/l did not necessarily have major liver injury. 18 This study is in agreement with the latter study, with mean ALT levels increasing with increasing grade of injury. But further studies with a larger sample size and inclusion of patients with grade 5 and 6 liver injuries are needed to achieve an authentic conclusion for the same.…”
Section: -13supporting
confidence: 82%
“…A study conducted by Tian et al found a trend that the more severe the liver injury of the patients, the higher the liver enzyme levels, but their study further demonstrated that patients with elevated ALT>100 U/l, AST>113 U/l did not necessarily have major liver injury. 18 This study is in agreement with the latter study, with mean ALT levels increasing with increasing grade of injury. But further studies with a larger sample size and inclusion of patients with grade 5 and 6 liver injuries are needed to achieve an authentic conclusion for the same.…”
Section: -13supporting
confidence: 82%
“…The serum activities of ALT and AST have been reported to be increased as a result of liver injury in patients developing severe hepatotoxicity (Beckett, 1989;Tian et al, 2012). Chemical and organic toxicants like crude oil are known to cause liver damage and precipitate elaboration of ALT and AST above the basal level in the serum (Chang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Some studies have shown an association between elevated liver enzymes and blunt liver trauma, but no consensus has been reached regarding its value in guiding management. 18,19 Imaging With improved access, availability, and sensitivity of imaging, as well as improved critical care management, there has been a shift in the management of hepatic trauma from surgical management to more NOM strategies. 20 Previous reports have shown that up to 86% of patients with hepatic trauma have stopped bleeding by the time of surgery, and in up to 67% of these patients, surgical intervention had no therapeutic value.…”
Section: Laboratory Studiesmentioning
confidence: 99%